2022
DOI: 10.1186/s12891-022-05771-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of walking speeds and durations on the plantar pressure gradient and pressure gradient angle

Abstract: Background Walking exercise has been demonstrated to improve health in people with diabetes. However, it is largely unknown the influences of various walking intensities such as walking speeds and durations on dynamic plantar pressure distributions in non-diabetics and diabetics. Traditional methods ignoring time-series changes of plantar pressure patterns may not fully capture the effect of walking intensities on plantar tissues. The purpose of this study was to investigate the effect of vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…Considering the clinical implications of the results of this study, plantar pressure changes with different walking speeds would be useful to recommend activities for patients with specific foot problems. For example, patients with forefoot pain should slow down, since a fast walking speed needs more range of motion of the first metatarsophalangeal joint, which increases the shear force contributing to skin breakdown [ 18 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the clinical implications of the results of this study, plantar pressure changes with different walking speeds would be useful to recommend activities for patients with specific foot problems. For example, patients with forefoot pain should slow down, since a fast walking speed needs more range of motion of the first metatarsophalangeal joint, which increases the shear force contributing to skin breakdown [ 18 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lakhdar et al [ 15 ] concluded that brisk walking has beneficial effects on anthropometric and biochemical parameters, physical performance, and glycemic control for diabetic patients. However, a fast walking speed can increase the plantar pressure at the forefoot and rearfoot areas [ 18 , 19 ], thereby increasing the risk of DFUs. The pronation of the foot or its side-to-side movement causes the foot to roll a bit inward with each step, with the big and second toes working to push off the foot while the other toes stabilize the foot.…”
Section: Introductionmentioning
confidence: 99%
“…Conducting the study, which looked at the relationship between walking speed and peak pressure gradient in healthy individuals, also in individuals with ITV will reveal valuable results 34 .…”
Section: Discussionmentioning
confidence: 99%
“…All kinematic variables were observed between the three environments that participants were asked to execute: (1) barefoot, (2) standard insole, and (3) innovative insole. The insole likely causes stabilization to the foot, but it is necessary to understand whether the magnitude of stabilization is significantly different in the three environments (1, 2, and 3) and whether this stabilization does not compromise functional and individual mobility [31].…”
Section: Kinematic Variablesmentioning
confidence: 99%